Perancangan Prototype Kran Wudhu Otomatis Berbasis Arduino Uno untuk Menghemat Air Menggunakan Sensor Ping - Jufrizel Jufrizel; Muhmammad Zakir (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
The waters are very important in human life, it can be seen from the level of human using water in the daily activities, one of them is to perform ablutions. During this time the manual ablution has the disadvantage waste of water and possibility the faucets are easily damaged because of frequent physical contact with the hand. To handle the problem of water wastage can be do by made a prototype of automated ablution faucets based arduino uno using ping sensors to avoid wastage of water and the risk of faucets easily damaged in ablution. The results obtained are already achieving the purpose of saving water in making ablution using control devices automatic faucet, it is proved by the volume of water required when using the automated system only ± 500 milli liters, when using of a manual faucets is ± 920 milli liters.Keyword: Arduino uno, relays, selenoid valve, ping sensor